Diagnostic Value of Modern Methods of Ocular Anterior Segment Visualization in Intumescent Cataract - O. L. Fabrikantov; S. I. Nikolashin; E. S. Pirogova (Oftalʹmologiâ)
Purpose: tо evaluate the diagnostic capabilities of optical coherence tomography (OCT), Scheimpflug camera and ultrasound biomicroscopy (UBM) in examining topography of the ocular anterior segment and lens in mature intumescent cataract. Patients and methods. 23 eyes with mature intumescent cataract were examined using OCT (RTVue-100, Optovue, USA), Scheimpflug camera (Pentacam HR, Oculus, Germany) and UBM (UD 8000, Tomey, Japan). We examined the anterior chamber depth, profile and magnitude of the anterior chamber angle, distance “trabecula-iris at 500 microns”, thickness of the liquid lenticular mass layer, lens thickness, Zinn ligament length within four segments, equatorial angle. Results. We managed to measure the anterior chamber depth using UBM and Scheimpflug camera. UBM measurement was 1.96 ± 0.14 mm, Scheimpflug camera — 1.91 ± 0.11 mm. We revealed narrowing of the anterior chamber angle up to 11.54 ± 2.19° in UMB examination, to 11.49 ± 2.17° in OCT measuring and to 11.63 ± 2.21° in examining by Scheimpflug camera. Distance “trabecula-iris 500” was 0.212 ± 0.037 mm in UMB examination, 0.218 ± 0.042 mm — by means of OCT, Scheimpflug camera measurement was unsuccessful. The rest parameters were examined only by UBM. The lens thickness was 5.26 ± 0.13 mm. The anterior layer of liquid lenticular mass was 0.85 ± 0.06 mm. Zinn ligament length in the outer segment was 0.708 ± 0.072 mm, in the internal segment — 0.731 ± 0.089 mm, in the superior segment — 0.704 ± 0.084 mm, in the inferior segment — 0.876 ± 0.089 mm. The equatorial angle in two opposite segments was 32.52 ± 0.92°. Conclusion. Ultrasound biomicroscopy has the biggest value in examining topography of the ocular anterior segment and lens in mature intumescent cataract, since only this method allows achieving the whole complex of data necessary to evaluate the swelling lens parameters. This can serve as a basis for developing the appropriate tactics of surgical intervention.